The Reality of e-learning at Palestine Technical University Kadoorie in Light of the Corona Pandemic from the Point of View of the Teaching Staff in Tulkram - Qareeb, Intisar Saleem (Journal of Educational and Psychological Sciences, 2022)
This study aimed to know the reality of e-learning at Palestine Technical University Kadoorie in light of the Corona pandemic; The study used the qualitative approach by conducting an interview with (15) faculty members, and after analyzing these data, the following results were reached: The university’s infrastructure is good but needs development, there is qualification and training by the university and the e-learning center before and during the Corona pandemic, There are obstacles related to technical problems, including power and internet outages, and there are psychological difficulties and pressures within the home quarantine, as well as previous experiences in the use of e-learning among the majority of the sample. The results also showed that the e-learning environment may be supportive for some courses, but not for all of them, especially those related to academics and applied sciences. Based on the results, a set of recommendations were developed, including the need to work on developing infrastructure, improving the educational environment, and purchasing licenses for some software that are used for e-learning, in order to advance the e-learning process and keep pace with educational development in the world, including teacher preparation programs and professional development programs for faculty members as courses And programs for distance education, explaining its mechanisms, teaching methods, evaluation methods and tests in distance education, activating the role of counseling programs through academics or psychological and social specialists to alleviate the anxiety of the Corona virus pandemic on students, by the available means (publications, remote lectures).
Keywords: reality; e-learning; corona pandemic; Palestine Technical University Kadoorie